Strain Energy Governed Damage Law for a Visco-Plastic Material - Chrzanowski, M. (Engineering Transactions, 1991)
The inelastic strain energy which was shown by other authors to correlate fatigue data is used as an independent variable in a differential law of damage growth. A special form of this law is discussed, and material constants are evaluated to fit experimental data for low-cycle fatigue and creep of 304 stainless steel at 650° 0. Since the main goal of this study is to develop the method of life prediction for a wide range of practical applications, both uniaxial and multiaxial states of stress are evaluated. In the farmer case the effects of rate of loading, strain/stress control, wave shape, mean strain and hardening are considered. The multiaxial state of stress has been illustrated by a special case of combined axial-torsional deformation. In all these situations the inelastic strain energy was calculated according to the viscoplasticity theory based on overstress (VBO), which was shown to describe the cyclic deformation of 304 stainless steel in room as well as in elevated temperatures.